PENERAPAN KONSEP ARSITEKTUR REGIONALISME PADA BANGUNAN AULA INSTITUT TEKNOLOGI BANDUNG - Sri Indriani Solehah; Ashadi Ashadi (Universitas Indraprasta PGRI, 2021)
Distinctive features in architecture need to be preserved because it is part of the ancestral cultural heritage that is now one of the privileges and richness of the nation's culture. Along with the times and technological advances, the architecture of typical buildings in each area has changed over time. Developments in life lines make human needs more complex, thus demanding to create a more supportive space. Bandung Institute of Technology (ITB) campus hall building is one of the buildings that is suspected to have a distinctive regional element. Seeing that, it is necessary to review the application of the concept of regionalism architecture in the building of ITB Bandung campus hall, in order to know how the application of regionalism architecture elements. With qualitative descriptive methods, the author will analyze the data by identifying and assessing the existence of architectural principles in case studies.